V-ATPase in glioma stem cells: a novel metabolic vulnerability - Alessandra Maria Storaci; Irene Bertolini; Cristina Martelli; Giorgia De Turris; Nadia Mansour; Mariacristina Crosti; Maria Rosaria De Filippo; Luisa Ottobrini; Luca Valenti; Elisa Polledri; Silvia Fustinoni; Manuela Caroli; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Glioblastoma (GBM) is a lethal brain tumor characterized by the glioma stem cell (GSC) niche. The V-ATPase proton pump has been described as a crucial factor in sustaining GSC viability and tumorigenicity. Here we studied how patients-derived GSCs rely on V-ATPase activity to sustain mitochondrial bioenergetics and cell growth. Methods V-ATPase activity in GSC cultures was modulated using Bafilomycin A1 (BafA1) and cell viability and metabolic traits were analyzed using live assays. The GBM patients-derived orthotopic xenografts were used as in vivo models of disease. Cell extracts, proximity-ligation assay and advanced microscopy was used to analyze subcellular presence of proteins. A metabolomic screening was performed using Biocrates p180 kit, whereas transcriptomic analysis was performed using Nanostring panels. Results Perturbation of V-ATPase activity reduces GSC growth in vitro and in vivo. In GSC there is a pool of V-ATPase that localize in mitochondria. At the functional level, V-ATPase inhibition in GSC induces ROS production, mitochondrial damage, while hindering mitochondrial oxidative phosphorylation and reducing protein synthesis. This metabolic rewiring is accompanied by a higher glycolytic rate and intracellular lactate accumulation, which is not exploited by GSCs for biosynthetic or survival purposes. Conclusions V-ATPase activity in GSC is critical for mitochondrial metabolism and cell growth. Targeting V-ATPase activity may be a novel potential vulnerability for glioblastoma treatment.